PERKEMBANGAN KEAGAMAAN PADA ORANG DEWASA - Syahputra, Dimas; Asna, Atikah (Cahaya Ilmu Bangsa Institute, 2024)
Religious psychology is a field that studies the relationship between individual psychological aspects and religious beliefs and practices. This research aims to explore the development of religious spirit in adults, as well as how psychological factors influence their religious attitudes and behavior. Adults, who often have a more mature under standing of religious values, demonstrate religious attitudes that tend to be stable and integrated into everyday life. This research found that religious attitudes in adults are not only influenced by spiritual experiences, but also by mature cognitive processes in choosing and maintaining religious values. The results showed that adults who have a high level of religiosity are more likely to adopt religious values as a guide to life, which has a positive impact on their mental health and psychological well-being. Additionally, there was a significant relationship between religiosity and mental help-seeking behavior, with religious individuals being more likely to seek support from religious leaders compared to secular mental health professionals. Through this analysis, it is hoped that it can provide deeper insight into the role of religious psychology in the lives of adults and its implications for their psychological well-being and social dynamics. This research also suggests the need for the integration of religious leaders in mental health support systems to increase the effectiveness of interventions for individuals experiencing psychological challenges.